You start with 2x -5>7 the you add five to both sides 2x-5+5>7 +5 2x.12 then divide both sides by 2 2x divided by 2 > and 12 divided by 2 and get x>6
Answer:
Option 4. x = 0
Step-by-step explanation:
we know that
The rule of the reflection of a point across the y-axis is equal to
(x,y) -----> (-x,y)
The rule for reflecting over the Y axis is to negate the value of the x-coordinate of each point, but leave the y-value the same
The coordinates of triangle PQR are
P(1, 4), Q(3, 6), and R(5, 2)
Applying the rule of the reflection across the y-axis we have
P(1, 4) -----> P'(-1, 4)
Q(3, 6) ----> Q'(-3, 6)
R(5, 2)----> R'(-5, 2)
The reflection line is the y-axis
Remember that the equation of the y-axis is x=0
therefore
The equation of the reflection line is x=0
The greatest common factor is 6. Thus means we divide every part of the expression by 6.
6x^2/6 = x^2
42x/6 = 7x
-18/6 = -3
Your new expression is 6(x^2 + 7x -3).
Answer: 6x+3y
Step-by-step explanation:
3x+3(x+y)= 3x+3x+3y=6x+3y